Use of a type IIB external skeletal fixator in experimental tarsocrural arthrodesis in dogs - Dórea Neto, Francisco De Assis; Oriá, Arianne Pontes; Padilha Filho, João Guilherme [UNESP]; Regonato, Everton; Moreno, Juan Carlos Duque; Canola, Júlio Carlos [UNESP] (UFBA - Universidade Federal da Bahia, 2012)
The aim of the present study was to evaluate the usefulness of type IIb external skeletal fixators with a transarticular pin in experimental tarsocrural arthrodesis. Twelve adult mongrel dogs of both sexes, ranging in age from two to five years and weighing 12 to 25kg, were used. The configuration of the fixator consisted in the application of a transarticular Steinmann pin and of centrally threaded pins to the proximal portion of the tibia and calcaneus and to the distal portion of the metatarsal bones. In addition, Schanz pins were inserted into the medial and lateral side of the tibia and into the medial side of the metatarsal bones. Radiographs were taken 15; 30 and 45 days after surgery. Bone fusion of the treated joints were observed at 30 days in all animals, and the implants were removed after 45 days. Loosening of the centrally threaded pins was observed in all groups, especially for those applied to the calcaneus. The configuration of the external fixator proposed here was found to be satisfactory in terms of bone union for all joints during the same period, irrespective of the weight of the animal.

O objetivo com este trabalho foi avaliar a utilização de fixadores esqueléticos externos do tipo IIb com pino transarticular em artrodeses tarsocrurais experimentais. Foram empregados 12 animais da espécie canina, machos e fêmeas, sem raça definida, adultos, com idades entre dois e cinco anos, peso entre 12 e 25kg. A configuração do fixador foi estabelecida com a aplicação de pino de Steinmann transarticular, pinos com rosca central na porção proximal da tíbia, calcâneo e distal nos metatarsianos, pinos de Schanz, também, foram aplicados na face medial e lateral da tíbia e na face medial dos metatarsianos. Os intervalos de tempo para as análises radiográficas foram 15; 30 e 45 dias do pós-cirúrgico. Foram observadas fusão das articulações que sofreram artrodese aos 30 dias em todos os animais, sendo, os implantes removidos aos 45 dias. Houve afrouxamento dos pinos de rosca central em todos os grupos, sobretudo os pinos aplicados no calcâneo. A configuração do fixador externo proposto por este trabalho, mostrou-se satisfatória para a união óssea de todas as articulações em um mesmo período, independentemente do peso do animal.
Artrodeses tarsocrurais experimentais em cães utilizando fixadores esqueléticos externos do tipo IIB
Keywords: cão; cirurgia experimental; fusão articular; pequenos animais; ortopedia veterinária; dog; experimental surgery; joint fusion; small animals; veterinary orthopedics